Cigarrinha-do-milho (Dalbulus maidis) e o complexo dos enfezamentos: características de transmissão, disseminação e controle - Pinto, Murilo Rafael (Universidade Federal de São Carlos, 2021)
In corn, the leafhopper, Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) is the vector of three pathogens: Spiroplasma kunkelii (corn stunt spiroplasma), Maize bushy stunt phytoplasma and maize streak virus (Maize rayado fino virus). With the expansion of the planted area and the cultivation of the second season corn, there was a change in the dynamics of sowing, allowing the presence of the hosts for a longer time in the field during the year, with direct influence on the incidence of this disease complex. Due to the high biotic potential, high potential for migration and significant damage, leafhoppers and this group of diseases that were considered as secondary pests, started to have a new understanding. As a consequence of the relevance of this new pest scenario, due to the challenge in practices for its effective control, Integrated Pest Management stands out for integrate management practices, looking for sustainability and application of techniques in addition to not just achieve population reduction, but rather, a multidisciplinary and systemic understanding of phytosanitary management.
Corn leafhopper (Dalbulus maidis) and the stunt complex: characteristics of transmission, dissemination and control
Keywords: Zea mays; Enfezamentos; Dalbulus maidis; Corn stunts; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE